PENGARUH MODEL PROBLEM-BASED LEARNING BERBASIS SIMULASI PHET TERHADAP PENINGKATAN KETERAMPILAN PROSES SAINS - Tamba, Julinar; Sitinjak, Erni Kusrini; Marbun, Juliaster (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
The purpose of this study was to determine the effect of the PhET Simulation-Based Problem-Based Learning model on Students' Science Process Skills (KPS) at SMAS Bani Adam A's. The study took place in June 2025 and the quasi-experimental method was a nonequivalent control group design. In this study, the sample was determined through purposive sampling where class X-3 was the experimental class and X-1 the control class with the same number of students, namely 30 students. The research instrument was a multiple-choice KPS test totaling 20 questions. Before being given treatment, a pretest was given and then a prerequisite test was carried out to ensure the data was normally distributed and homogeneous. Given in both classes, the average score was 47.6 in the experimental class and 48 in the control class, each having a standard deviation of 15.35 and 15.5, respectively. Then given treatment, the posttest results showed an average score of 78.16 in the experimental class and 63.66 in the control class with standard deviations of 10.94 and 13.38, respectively. The data analysis used a one-tailed t-test at a significance level of α = 0.05, indicating that t count > t table. The results demonstrated a significant difference in both classes, thus supporting the application of the PhET Simulation-Based Problem-Based Learning model to the KPS.